2020
DOI: 10.5650/jos.ess19228
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Rich Tree-borne Oilseeds from Forests of Assam, India

Abstract: Introduction Edible oils are structurally composed of tri-acylglycerol molecules formed by unsaturated oleic, linolenic, linoleic acids etc. and saturated fatty acids capric, lauric, myristic, palmitic, stearic etc. esterified to Glycerol units 1. As oils of seeds contain mainly unsaturated fatty acids therefore seed oils are preferred more as an alternative to saturated animal fats like bacon, butter and hydrogenated vegetable products. Linoleic, linolenic and oleic acids are called the essential fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the present study, oleic acid was identified as the most abundant MUFA in all the treatments. Oleic acid has previously been reported as the most abundant fatty acid in both insects [ 40 ] and humans [ 48 ]. It is important to note that there are important benefits associated with the presence of oleic acid in living organisms, for example, in insects, it regulates the fluidity of cell membranes by serving as a major precursor for the biosynthesis of waxes and semiochemicals [ 49 ], while in humans, it serves as a cholesterol-lowering agent associated with heart diseases [ 49 ] and as an anticancer and anti-inflammatory agent [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, oleic acid was identified as the most abundant MUFA in all the treatments. Oleic acid has previously been reported as the most abundant fatty acid in both insects [ 40 ] and humans [ 48 ]. It is important to note that there are important benefits associated with the presence of oleic acid in living organisms, for example, in insects, it regulates the fluidity of cell membranes by serving as a major precursor for the biosynthesis of waxes and semiochemicals [ 49 ], while in humans, it serves as a cholesterol-lowering agent associated with heart diseases [ 49 ] and as an anticancer and anti-inflammatory agent [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are important benefits associated with the presence of oleic acid in living organisms, for example, in insects, it regulates the fluidity of cell membranes by serving as a major precursor for the biosynthesis of waxes and semiochemicals [ 49 ], while in humans, it serves as a cholesterol-lowering agent associated with heart diseases [ 49 ] and as an anticancer and anti-inflammatory agent [ 50 ]. Additionally, it plays a crucial role during pregnancy-lactation [ 51 ], promotes cell viability [ 52 ], and serves as a source of energy and a precursor for the biosynthesis of linoleic acid required for production of arachidonic acid involved in cell regulation [ 48 ]. Thus, the detection of oleic acid in all the oils and bakery products (cookies) suggests that it may contribute to their overall nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…Results in the table (4) showed the phenolic compounds of Moringa peregrina seeds oil, Terminalia bellerica seeds oil, and Tiger nut oil determined by HPLC, analysis it could be noticed that oleuropin was the major phenolic compounds 10.65, 15.76, and 14.51 ppm in the same above samples, respectively followed by salicylic acid (4.43) and (pyrogallol 2.48 ppm) in Moringa, ellagic acid was1.33 and ferulic acid 1.11ppm in Terminalia and ferulic acid 1.64, ellagic acid was 1.55 ppm in Tiger nut [ 34,35]. [2,10,9,17,33].…”
Section: Discussionmentioning
confidence: 92%
“…64, No. 9 (2021) On the other hand, linolenic acid recorded the lowest value in the unsaturated fatty acid, it was 0.02, 0.12, and 0.15 in Moringa seeds oil, Terminalia seeds oil, and Tiger nut oil, respectively, also the ratio of the total unsaturated /total saturated fatty acid (Tus/ Ts) was 4.25, 3.25 and 3.48%, respectively [3,1,8,10,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation